VOR gain of lateral semicircular canal using video head impulse test in acute unilateral vestibular hypofunction: A systematic review - Alfarghal, Mohamad; Algarni, Mohammed Abdullah; Sinha, Sujeet Kumar; Nagarajan, Aishwarya (Frontiers in Neurology, 2022)
Introduction: Acute unilateral vestibular hypofunction is characterized by sudden onset of vertigo or dizziness, vomiting/nausea, gait instability, and nystagmus, this is commonly described as acute vestibular syndrome and usually attributed to vestibular neuritis; however up to 25% of AVS cases can be attributed to posterior circulation strokes . VHIT can assess the VOR gain in various vestibular disorders. Method: A literature search was conducted in databases, including Google Scholar, PubMed, and Web of Science. All the articles that define vHIT and acute vestibular syndromes, vestibular neuritis were considered . The searches were limited to studies with full-text availability, published in English, and including human subjects. Search words such as "head impulse test, video head impulse test, VOR , acute vestibular syndrome, acute vestibular hypofunction, vestibular neuritis, etc” were entered into different databases in different combinations using Boolean operators such as AND, OR, NOT. Results: Searches across different databases resulted in 245 topic-related records. 56 articles were identified and screened after duplicate removal and applying inclusion and exclusion criteria. After screening for full text, as per the eligibility criteria, 21 articles were found to be eligible for the systematic review. Among the remaining studies, 6 articles were excluded due to different specific reasons. Total 15 articles were included for this systematic review. The mean VOR gain for the patients with vestibular neuritis was 0.48±0.14 for the ipsilesional ear, whereas the mean VOR gain was greater than 0.80 in the contralesional ear for all the patients with acute vestibular neuritis. In patients with PICA infarction the VOR gain for ipsilesional side ranged between 0.87- 0.94 and for the contralesional side ranged between 0.84-0.93. In patients with AICA lesion the mean VOR gain was variable. Based on the above mean VOR gain findings, the authors propose the following adjective description scale for the VOR gain VOR gain: above 0.80 normal VOR gain, 0.79 -0.70 mild VOR gain Loss, 0.69-0.40 moderate loss, 0.39-0.20 severe, and less than 0.20 profound loss Abbreviations: AVS =Acute Vestibular Syndrome, AICA =Anterior Inferior Cerebellar Artery, PICA =Posterior Inferior Cerebellar Artery, SCC=Semicircular Canal, VHIT=Video Head Impulse Test, VOR =Vestibulo-Ocular Reflex